Hydrogeochemical characterization of groundwater in a coastal area, central western Senegal - Ndoye, Seyni; Diedhiou, Mathias; Celle, Helene; Faye, Serigne; Baalousha, Mohammed; Le Coustumer, Philippe (Frontiers in Water, 2023)
One of the most serious problems affecting coastal aquifers is seawater intrusion. Senegal is currently facing an increased demand for freshwater resources due to population growth and economic development in coastal areas. In areas affected by saltwater contamination, chloride concentrations as high as 8880 mg/L were measured in groundwater samples taken from wells near the coastal zone, indicating deterioration in water quality. Our study aims to identify the zones of degradation of the water quality by determining the chemical composition of groundwater and the geochemical processes controlling the chemical patterns. Hydrogeochemical (Piper and Chadha diagrams, chloroalkaline indices, normalized bivariate plots) and multivariate statistical (Hierarchical cluster analyses) techniques were used. Forty-two groundwater samples were collected and analyzed for concentrations of major and some minor ions, electrical conductivity (EC), total dissolved solids (TDS), temperature, and pH. From samples we were able to establish a diagnosis of the very heterogeneous quality of the groundwater in this area. The average pH of the groundwater is 7.6 and about 80% of the groundwater samples have a TDS below 1000 mg/L. On the other hand, the EC values are very heterogeneous with very high conductivities in coastal areas. Approximately, 80% of the groundwater samples have a TDS less than 1000 mg/L and EC values are very heterogeneous. The dominant water types in the study area are Na-Cl water type (less than 10% of the samples) characteristic of the spatial evolution of groundwater salinization from west to east, mixed Ca-Mg-Cl due to fresh water/salt water contact and Ca-Mg-HCO3 water-type (nearly 56% of the samples) to the east. A hydrogeochemical zonation of the aquifer, based on the presence of different water families allows us to visualize the highly degraded (west), mixed (center) and healthy (east) zones. Chloroalkaline indices and normalized bivariate plots show that the chemistry of groundwater is controlled mainly by water-rock interaction and evaporation processes. As water-rock interaction processes, dissolution of carbonate and evaporite, weathering of silicate, ions exchange regulates major ion chemistry.